The Catholic Reform: Towards A Modern Symbiosis Of Religion And Politics - Elezović, Dalibor M.; Kocić, Marija V. (Sociološki pregled, 2020)
The paper discusses the Catholic Reform as a period of change in the Roman Catholic Church in the 16th and 17th centuries, which opposed the Reformation, and which contained a symbiosis of religion and politics. On the path of consolidation, the Roman Catholic Church did not opt for a gospel approach, and therefore implemented a significant part of its measures precisely through political means, which were sometimes aggressive and at times sophisticated. Significant aspects of the Reform were closer to political action than internal reconstruction and reorganization, with such measures the Roman Catholic Church sought to consolidate and protect against Protestantism.
Keywords: Catholic Reform; religion; politics; Catholicism; Protestantism